Rekayasa Perangkat Lunak Kalkulator Berbasis Mobile Guna Memudahkan Berhitung - Munawaroh, Munawaroh; Priambodho, Anggra; Muharto, Derry Bagus; Ramadhani, Farah Cahyana; Rahmadila, Laita; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2022)
In calculating a number we used to use a calculator as a tool in calculating. But we often ignore calculators when traveling. With technological developments, mobile devices are very often for us to carry to travel far and close. Therefore the author is here to answer the problem by analyzing the behavior of the community in calculating when traveling. In creating a calculator application the author needs tools such as Android Studio, MySQL, SDK, JDK and Visual Studio Code to create Android applications and writers using Java as a programming language because it is one of the most popular programming languages in making Android and Java applications also has advantages (1) Easy to develop, (2) also provides convenience in writing code, (3) dynamic, (4) object -oriented and (5) multiplatforms. So that we can use the mobile devices as a calculation aid to replace the electronic calculator. With the calculator in the mobile device we can use a calculator anywhere and anytime.